Covid-19 Lockdown and Its Impact on Air Pollution - NIVEDITHA, A. SANKARI; MDS, DR. BALAJI GANESH S; ARIVARASU, LAKSHMINARAYANAN (The journal of contemporary issues in business and government, 2020)
Air pollution is one of the major problems of recent decades which has a serious toxicological impact on human health and the environment. Air pollution is defined as all destructive effects of any sources which contribute to the pollution of the atmosphere or deterioration of the ecosystem. Air pollution is caused by both human interventions and/or natural phenomena. Air pollution is a mixture of solid particles and gases in the air. It is a type of environmental pollution that affects the air and is usually caused by smoke or other harmful gases. The sources of pollution vary from small units of cigarettes and natural sources such as volcanic activities to large volume of emission from motor engines of automobiles and industrial activities. During this lockdown period, there was a dramatic decrease in air pollution in different parts of the world. This is primarily due to lockdown of industrial establishments. The impact of human civilization during the pandemic provides evidentiary data. There was significant improvement in global air pollution. The aim of this review is to understand the correlation between COVID-19 lockdown and its impact on air pollution.